Narratives, Images and Objects of Piety and Loss in Brittany - Coughlin, Maura (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract How can material culture studies offer new perspectives on the study of late-19th-century art in France? How can the work of contemporary artists animate a collection of historical and locally specific objects? This paper takes up these questions by a close reading of an installation in Saint-Brieuc, along with the collections of two ecomuseums in Brittany and several other historical sites in terms of a politics of display and commemoration. It further engages the collections in a dialogue about historical sites, photographs and paintings of religious ritual in late-19th-century Brittany that focus upon everyday rituals of memory and mourning.